(untitled) (Baghdad Science Journal, 2023)
The medicinal plants (Astragalus species) have been used traditionally as anti-inflammatory, antioxidant, and Anti-diabetics. The current research investigates the phytochemistry and some biological activity of methanol extract of different parts of Astragalus bruguieri Bioss., a wild medicinal plant grows on Safeen mountain, Erbil, Iraq. The methanol extracts of A. bruguieri were analyzed for total phenolic, flavonoid, and saponin contents. In-vitro antioxidant activity was analyzed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Furthermore, the plant extracts were examined for in-vitro enzyme inhibitory activity and in-vivo sub-acute toxicity. The results have shown the highest total phenolic (28.83, 20.62 mg GAEs/g extracts) contents, in the leave and root extracts, respectively. While the highest total Flavonoid (50.08, 44.01 mg REs/g) contents, were found in the extracts of aerial parts and leaves, respectively. The total saponin was higher (25.33, 23.18 mg GAEs/g extracts) in the roots and aerial parts, respectively. In-vitro antioxidant measurement by (DPPH) assay showed leaves as superior part in this activity (42.19mg TEs/g extract), while antioxidant evaluation by (ABTS) assay indicated roots as the most active part (86.90mg TEs/g extract). The α-glucosidase and α-amylase inhibitory activity were found as 0.45-0.67, and 1.2-1.8 mmol ACAEs/g, respectively. The oral acute toxicity test indicated the safety of 600mg/kg dosage of different parts of A. bruguieri on albino rats without behavioral abnormality or mortality. The current study is considered as the first report on the A. bruguieri as a possible new source of biocompatible material for many industrial products.